2007
DOI: 10.1021/jf063085h
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Characteristics and Antioxidant Properties of Fresh and Processed Sea Cucumber (Cucumaria frondosa)

Abstract: The antioxidant activity of fresh and rehydrated sea cucumber (Cucumaria frondosa) samples with/without internal organs was evaluated for the first time. In addition, their proximate, amino acid, and fatty acid compositions were examined. Rehydrated sea cucumber samples in distilled water were prepared from oven-dried products. All samples contained 83-90% moisture, but showed a significant difference among groups in their protein and lipid contents. Glutamic acid was the predominant amino acid in sea cucumber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
160
8
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(204 citation statements)
references
References 25 publications
31
160
8
5
Order By: Relevance
“…Holothuria grisea showed ca. twice more lipid than the sea cucumber Cucumaria frondosa analized by Zhong et al (2007). Total lipid of H. grisea was slightly higher than the lipid content (8% dw) recorded by Betchel et al (2013) in the giant red sea cucumber Parastichopus californicus, and similar to the contents reported by Wen et al (2010) for Thelenota anax (9.9% dw) and Actinopyga caerulea (10.1% dw), two edible sea cucumbers from China.…”
Section: Lipidsupporting
confidence: 71%
“…Holothuria grisea showed ca. twice more lipid than the sea cucumber Cucumaria frondosa analized by Zhong et al (2007). Total lipid of H. grisea was slightly higher than the lipid content (8% dw) recorded by Betchel et al (2013) in the giant red sea cucumber Parastichopus californicus, and similar to the contents reported by Wen et al (2010) for Thelenota anax (9.9% dw) and Actinopyga caerulea (10.1% dw), two edible sea cucumbers from China.…”
Section: Lipidsupporting
confidence: 71%
“…Normally the moisture content in most of the sea cucumbers were in the range of 84% to 91% [24], 83% to 86% in Isostichopus sp [34], 81% to 85% for H. tubulusa [9], even higher than present study as reported 89% to 90% in Parastichopus sp [35] and 87% to 90% in Cucumaria frondosa [31]. Moisture percentages in various studies can be link to due to collection time of year, environmental factors, geographical variations and feeding behaviour of respective species [35].…”
Section: Proximate Compositionscontrasting
confidence: 40%
“…Parastichopus californicus, a cold water species that harvested in Alaska had higher EPA (22.60%) and lower ARA (7.10%) [7]. EPA constituted for 46.10% in body wall of fresh Cucumaria frondosa, the orange-footed sea cucumber, a temperate species in North-Atlantic Ocean [31]. Fatty acid composition on abyssal sea cucumbers, Abyssocucumis abyssorum, Peniagone vitrea and Protankyra brychia, also reported lower ARA compared to EPA [32].…”
Section: Polyunsaturated Acids (Pufas)mentioning
confidence: 99%
“…(Chen, 2005). , , (Liu et al, 1984;Fredalina et al, 1999;Hankenson et al, 2000;Sun et al, 1991), (Fredalina et al, 1999;Zhong et al, 2007 ). 3 , 25 (Bousquet et al, 2008).…”
Section: 서 론unclassified